1977
DOI: 10.1016/0035-9203(77)90145-6
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of intestinal amoebiasis and vaginal trichpmoniasis with panidazole and its comparison with metronidazole

Abstract: A dose range study in 18 patients suffering from intestinal amoebiasis and treated with doses of panidazole between 1.0 and 2.0 g per day for six days revealed that the best therapeutic results were obtained with the higher dose. This dose was then compared with metronidazole, at the same dose, in a clinical trial in 100 patients with intestinal amoebiasis. Cure rates were 68% and 80% for the two drugs respectively. In 100 cases of vaginal trichomoniasis treated with panidazole at the dose of 1.0 g per day for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

1983
1983
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Three trials stratified participants during the analysis of outcomes into those with acute amoebic dysentery and those with non‐dysenteric amoebic colitis (Botero 1974; Botero 1977; Swami 1977). …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Three trials stratified participants during the analysis of outcomes into those with acute amoebic dysentery and those with non‐dysenteric amoebic colitis (Botero 1974; Botero 1977; Swami 1977). …”
Section: Resultsmentioning
confidence: 99%
“…Two trials reported the duration of time from start of treatment to disappearance of E histolytica from stools (Naoemar 1973; Pudjiadi 1973). Four trials reported on the number of stools passed at different periods: during treatment (Savas‐Erdeve 2009); after treatment (Pudjiadi 1973); and during treatment and on follow‐up after treatment (Botero 1977; Tripathi 1986), while another reported average daily frequency of stools on admission and at the end of days 5 and 10 of treatment (Asrani 1995). One trial assessed clinical and parasitological outcomes jointly as ‘cure' (Prasad 1985); only dichotomous outcomes were included in the analysis because of inconsistency in reporting continuous data (see Table 18).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations